Development of a model of information process management in the information and educational environment of preschool education organizations - Aitymova, Aliya; Iklassova, Kainizhamal; Abildinova, Gulmira; Shaporeva, Anna; Kopnova, Oxana; Kushumbayev, Agibay; Smolyaninova, Svetlana; Aitymov, Zhanat; Karymsakova, Anara (Eastern-European Journal of Enterprise Technologies, 2023)
One of the important elements of the information infrastructure of educational institutions is the information and educational environment. The information and educational environment of preschool education organizations has its own characteristics, which must be taken into account when building a model for managing information processes. The object of study in this work is the information and educational environment for preschool education organizations. The problem to be solved is the need to develop a model for managing data and information processes, which will allow determining the learning outcomes of preschoolers and adjusting individual work with them. The introduction of the developed model allowed to reduce the time spent on adjusting individual work with students by 30 %. These results are explained by the optimization of information processes, as well as improved monitoring of the formation of skills of preschoolers and a reduction in the time for its implementation. When monitoring for each child, 211 indicators are examined. There are 633 indicators per year for three monitoring, in aggregate, per one child. By default, the data is entered into Microsoft Excel and processed manually. However, a large number of entries slows down the processing of Microsoft Excel data and increases the chance of errors. The use of this model will make it possible to carry out calculations automatically, save data and generate reports for each child or group of children. The developed model can be used in information and educational environments for preschool education organizations in order to improve the efficiency of monitoring and managing educational processes